Bandwidth Management Analysis Using the HTB (Hierarchichal Token Bucket) Method - Noviyan (Universitas Putra Indonesia YPTK Padang, 2021)
Internet in today's era is one of human needs, because it requires a large bandwidth. Bandwidth usage is basically a measure of the performance of an organization. In this study, the problem to be discussed is how the bandwidth management process in PT. Mainstay Partner Achievement. The purpose of this management process is to manage the balance of download or upload access. The method used in solving this problem is the Hierarchical Token Bucket (HTB) method. This method is widely used to solve problems with Internet connections, maximizing bandwidth usage. The Hierarchical Token Bucket (HTB) method is one of the methods designed to be able to perform bandwidth management well, where this algorithm applies queuing discipline which has advantages in limiting traffic at each level and classification, so that bandwidth that is not used by high levels can be used. or divided by lower levels. In the discussion, the HTB method is able to provide maximum results in bandwidth management. Benefits From these results network performance will be more optimal at PT. The mainstay of Achievement Partners can work even better